2019
DOI: 10.1111/ajag.12754
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, frailty and outcomes in geriatric rehabilitation

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
(21 reference statements)
2
18
1
Order By: Relevance
“…This indicates that psychological resilience does not play a mediating role. This was unexpected since, in previous studies, the associations with limitations in ADLs (Yang and Wen, 2015;Hardy et al, 2004) and (pre)frailty (Kohler et al, 2020;Wong et al, 2021) were found. Kohler et al (2020), for example, found an association in 65 year olds in geriatric rehabilitation using the Brief Resilience Scale (Smith et al, 2008) and the Frailty Index from comprehensive geriatric assessments (Searle et al, 2008).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…This indicates that psychological resilience does not play a mediating role. This was unexpected since, in previous studies, the associations with limitations in ADLs (Yang and Wen, 2015;Hardy et al, 2004) and (pre)frailty (Kohler et al, 2020;Wong et al, 2021) were found. Kohler et al (2020), for example, found an association in 65 year olds in geriatric rehabilitation using the Brief Resilience Scale (Smith et al, 2008) and the Frailty Index from comprehensive geriatric assessments (Searle et al, 2008).…”
Section: Discussionmentioning
confidence: 67%
“…This was unexpected since, in previous studies, the associations with limitations in ADLs (Yang and Wen, 2015;Hardy et al, 2004) and (pre)frailty (Kohler et al, 2020;Wong et al, 2021) were found. Kohler et al (2020), for example, found an association in 65 year olds in geriatric rehabilitation using the Brief Resilience Scale (Smith et al, 2008) and the Frailty Index from comprehensive geriatric assessments (Searle et al, 2008). However, it is clear that it is difficult to compare our communitydwelling sample with a geriatric population and with different measurements for both resilience and frailty.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Our hypothesis is that the inability of keeping the head up, being unable to stand or raising up the arms, is an expression of severe illness and /or lack of resilience and/or frailty. Since these three factors are predictors of mortality [ 19 22 ], we hypothesize that the hanging chin sign and the absence of PA view and lateral view are predictors of mortality as well.…”
Section: Introductionmentioning
confidence: 99%